Antidepressant, Anxiolytic and Neuroprotective Activities of Two Zinc Compounds in Diabetic Rats - Cavalcanti, Christiane Leite; Gonçalves, Maria Conceição Rodrigues; Alves, Adriano Francisco; de Araújo, Emmanuel Veríssimo; Carvalho, Jader Luciano P.; Lins, Priscilla Paulo; Alves, Raquel Coutinho; Soares, Naís Lira; Pordeus, Liana Clebia Morais; Aquino, Jailane Souza (Frontiers in Neuroscience, 2020)
Behavioral disorders affect most diabetic patients and Zinc(Zn) has been used among adjuvant therapies for involvement in the etiology of depression and anxiety, however the results are still controversial. The objective of this study was to compare the antidepressant, anxiolytic and neuroprotective activity of the supplementation of two Zn compounds in an animal model of Diabetes Mellitus type 1 (DM1). Thirty-eight (38) adult rats were randomized into four groups: Control (C; n = 8); Diabetic (D; n = 10); Diabetic Zn Sulfate Supplement (DSZ; n = 10) and Diabetic Zn Gluconate Supplement (DGZ; n = 10). The DSZ group received Zn sulfate supplementation and the DGZ group received Zn gluconate supplementation at a dose of 15 mg/kg for 4 weeks. Data (mean ± SEM) were analyzed by the Mann-Whitney test with a significance level of p<0.05. The results indicate that Zn gluconate supplementation in diabetic animals presented an antidepressant effect demonstrated through the results obtained in the Forced Swim Test, and neuroprotective effect by attenuating alterations in the cerebral cortex; while Zn sulfate supplementation in diabetic animals showed an anxiolytic effect demonstrated by the results obtained in the open field test and the elevated plus maze test. Considering the set of results, supplementation with both zinc compounds showed neurobehavioral benefits in diabetic animals with different effects depending on the type of anion associated with Zn.